ANALISA PENGARUH GAYA KEPEMIMPINAN, BUDAYA LINGKUNGAN KERJA DAN PENILAIAN TERHADAP KINERJA KARYAWAN LEMBAGA PENDIDIKAN - Nani susilawati; Muhammad Ichwan Hamzah (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2025)
The purpose of this study was to analyze the results of multiple regression analysis, which showed that leadership style, environmental culture, and assessment had a positive and significant influence on employee performance at the Melbourne Institute of Language Studies. The independent variable with the greatest influence on employee performance was environmental culture. This was evidenced by the t-test results, which were higher than the other independent variables, at 5.099 with a significance level of 2.012. The estimated regression model in this study indicated that the independent variables explained 80.9% of the total, while the remaining 19.1% was explained by factors outside the model.